New Horizon-s for the European Energy Union - Tsvetanov, Ivan; Toskov, Ivaylo (Research Papers, 2019)
The presented study is dedicated to the interdependencies between the European Energy Union (the EEU) and the European Union Framework Programme for Research and Innovation “Horizon 2020”, which is one of the key tools for achieving the EEU objectives. The main EU legislative acts, which together form the Energy Union Package, are pointed out and briefly analysed. Significant attention is given to the five fundamental dimensions of the European Energy Union, and in their context are visualised the different instruments necessary for and serving the achievement of the Union’s objectives. The foundations and the legal framework of the Horizon 2020 Programme are established. By using the methods of analysis and synthesis the relation between the objectives of the EEU and the Horizon 2020 Programme is visualised, with particular attention to the 2016-2017 Horizon 2020 Work Programme. Finally, several main conclusions that come as a result from the research are formulated.